Group Incentives for the Public Good : A Field Experiment on Improving the Urban Environment - Newman, Carol (World Bank, Washington, DC, 2019)
How to maintain communal spaces is an important concern in many developing countries, particularly in urban environments. But what strategies can communities use to overcome the public goods problems involved in maintaining their local environment? This paper investigates whether changing the incentives for a subset of the community to contribute to the public good can lead to a shift to a more efficient equilibrium for the community as a whole. The analysis uses a randomized controlled trial to test the effectiveness of a program called "Operation Clean Neighborhood," which targets established community-based organizations and encourages them, through social recognition and low-value, in-kind incentives, to work toward keeping their neighborhoods clean, with the ultimate goal of reducing flooding in these areas. The findings show that, after one year, the intervention was effective in engaging communities and improving the cleanliness of the neighborhood. There is also evidence that this leads to reduced levels of flooding. The analysis uncovers important differences in the effectiveness of the program between areas that have had increased investment in drainage infrastructure and those that have not. It also addresses the issue of spillovers, an important consideration in densely populated urban centers.